LAYANAN PERPUSTAKAAN PERGURUAN TINGGI DIMASA PANDEMI COVID-19 - Fransisca, Ni Kadek Adelia Ayu; Ginting, Richard Togaranta; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi; Vol 2 No 2 (2022), 2022)
The purpose of this research is to find out a concept of digital services that can be done and provide analysis in the application of communication to online services from university libraries in terms of providing services to students. The method in this study uses a literature study on scientific concepts related to library science and analysis of publications carried out by library institutions during the pandemic. Research data obtained through observations on several library websites. The data is processed and then presented in descriptive form. The result is the need for library services with digital concepts to make it easier for users to find information online. keywords: college library, library service, covid-19 pandemic, digital library